Defining and classification of the soft projects as a base for their scope planning - Кондратов, Сергей Алексеевич; Аль Хамадани, Джамал Мохаммед (Technology audit and production reserves, 2015)
On the basis of deterministic model in the form of a system of nonlinear equations it is developed a "soft" model of stationary process of benzene nitration with a mixture of nitric and sulfuric acids in the reactor of ideal mixing, which allows to take into account the effect of uncertainty of input variables of the process on output variables: stationary temperature and conversion degree. The model algorithm is random assignment of input variables: speed and the heat of reaction and heat loss coefficient of the probable range of admissible values and solving the system of equations of the model for given values of regulate parameters and random allowable value of residence time. The model is visualized as a bitmap image of the points on the plane and allows to take into account the uncertainty of input factors, such as the range of the lower and upper boundaries of the bitmap image ("thick line"). It was established that a decrease with increasing conversion module and its increase with increasing concentration of the waste sulfuric acid are occurred for the adiabatic and isothermal processes. However, in an adiabatic process, depending on the module, there is a significant increase in temperature significantly superior to the standard values (50-70 °C), even when the module is 12. Increasing the temperature of the mass in inlet from 20 to 40 °C also leads to significant increase in the degree of conversion and temperature the reactor outlet. With increasing the residence time is observed narrowing of the upper and lower boundaries of the fixed conversion rate and leveling of uncertainty.